The Curator of the Imperial University in the system of national education of the Russian Empire in the ﬁrst half of the nineteenth century - Andreev Andrei (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The present article is devoted to the study of collective portrait of The Curator of the Imperial universities in Russia in the ﬁrst half of the 19 th century in the context of domestic policy and on the background of the development of universities in the Europe. The author makes the conclusion about the existence of three generations of The Curators. Each generations of The Curators had a particular management skills, social connections and cultural competencies. The ﬁrst generation of The Curators (the Curarors-founders) have tried to link the University world of Russia and Europe. A distinctive feature of the second generation of The Curator (the Curators-bureaucrats) began their intervention in the learning process within their own universities, which signiﬁ cantly aﬀected the freedom of teaching and learning in universities of Russia. Finally, the third generation of The Curators had created a new forms of University life after the introduction of the University Statute of 1835.